Manuale di linguistica sarda. - Blasco Ferrer, Eduardo (Manuals of romance linguistics., 2016)
The series Manuals of Romance Linguistics (MRL) aims to present a comprehensive, state-of-the-art overview of Romance linguistics. It will comprise approximately 60 volumes that can either be consulted individually or used as a series of books providing a detailed overall picture of the current state of research in Romance linguistics. A special focus will be placed on the presentation and analysis of the smaller languages, the linguae minores.